Irreducible intussusception. Intestinal resection in a case of hemophilia A - Rosa, A F; López, G; Lorenzo y de Ibarreta, J; Pérez Scremini, A (Cirugía del Uruguay, 1972)
The paper describes a case of intestinal invagination in a child on whom surgery was successfully performed in spite of hemophilia. The hemotherapeutic treatment is discussed.